Analysis Of E-Marketing Implementation In Enhancing The Sales Of Mudharabah Savings Products From An E-Commerce Perspective: A Case Study Of BSI Kc Metro A Yani - Purnama Sari, Anisa; Novita Sari, Linda; Nur Cahyati, Nur; Tiara Sari, Putri; Alfiansyah, Alfiansyah Imanda Putra (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
This study aims to examine the implementation of e-marketing in enhancing the sales of Mudharabah savings products from an e-commerce perspective, using BSI KC Metro A Yani as a case study. The research adopts a qualitative method, using data from BSI KC Metro A Yani’s customers and gathering in-depth information from its employees. Data collection techniques included interviews and document analysis, while data analysis was conducted using the Miles and Huberman approach.. The findings reveal that the implementation of e-marketing at BSI KC Metro A Yani has significantly increased the sales of Mudharabah savings products. Through effective strategies, the bank successfully expanded its market reach, attracted new customers, and boosted transaction volumes. Despite encountering several challenges, the solutions implemented effectively addressed these issues. By continuously innovating and adapting to technological advancements, BSI KC Metro A Yani has been able to sustain and even enhance its success in leveraging e-commerce for marketing Islamic banking products